THE INFLUENCE OF THE SELF ASSESSMENT SYSTEM, TRAINING METHODS AND TRAINING MATERIALS ON THE PERFORMANCE OF TAX VOLUNTEERS - Zahir, Aziz Malikuz; Zahroh, Fatmawati (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2023)
The development of taxation is constantly changing over time. The self-assessment system is a big step forward in the field of taxation where it is hoped that taxpayer awareness will increase. With the existence of a self-assessment system, the Directorate General of Taxes recruits tax volunteers to assist in the proper implementation of the self-assessment system. Therefore good training will improve the performance of tax volunteers, especially in terms of training methods and training materials that will be provided to tax volunteers. The purpose of this study was to determine the effect of the self-assessment system, training methods and training materials on the performance of tax volunteers. In this study using quantitative research. This research uses smart pls 4 software, the data collection instrument was a questionnaire measured by a Likert scale. This study has a sample of 160 respondents, namely tax volunteers at the Directorate General of Taxes (East Java Regional Office III). The results of this study indicate that the self- assessment system affects the performance of tax volunteers, training methods affect the performance of tax volunteers, and training materials also affect the performance of tax volunteers.